All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 206746 by sonukgindia last updated on 23/Apr/24
Answered by A5T last updated on 23/Apr/24
f(2)+2f(−1)=2...(i)f(−1)+2f(12)=−1...(ii)f(12)+2f(2)=12...(iii)2×(iii)−(ii):4f(2)−f(−1)=2...(iv)2×(iv)+(i):9f(2)=6⇒f(2)=23
Answered by mr W last updated on 24/Apr/24
f(x)+2f(11−x)=x...(i)f(11−x)+2f(x−1x)=11−x...(ii)f(x−1x)+2f(x)=x−1x...(iii)(iii)into(ii):f(11−x)+2[x−1x−2f(x)]=11−xf(11−x)=4f(x)+11−x−2(x−1)xthisinto(i):f(x)+2[4f(x)+11−x−2(x−1)x]=x⇒f(x)=19[x−21−x+4(x−1)x]f(2)=19[2−21−2+4(2−1)2]=23✓
Terms of Service
Privacy Policy
Contact: info@tinkutara.com